2013
DOI: 10.2337/db12-0624
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of A−β+ Ketosis-Prone Diabetes

Abstract: A−β+ ketosis-prone diabetes (KPD) is an emerging syndrome of obesity, unprovoked ketoacidosis, reversible β-cell dysfunction, and near-normoglycemic remission. We combined metabolomics with targeted kinetic measurements to investigate its pathophysiology. Fasting plasma fatty acids, acylcarnitines, and amino acids were quantified in 20 KPD patients compared with 19 nondiabetic control subjects. Unique signatures in KPD—higher glutamate but lower glutamine and citrulline concentrations, increased β-hydroxybutyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
50
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 37 publications
5
50
0
2
Order By: Relevance
“…There was no case of diabetic ketoacidosis as none of our patients showed the clinical pattern that characterizes ketosis prone diabetes from patients in the same unit [30,31]. Further steps towards improved diagnosis in this heterogeneous patient group may require both C-peptide and GADA determinations, while additional markers could be developed following the recently described alterations in amino acid metabolism [32], in combination with determination of PAX4 risk haplotypes [33]. …”
Section: Discussionmentioning
confidence: 99%
“…There was no case of diabetic ketoacidosis as none of our patients showed the clinical pattern that characterizes ketosis prone diabetes from patients in the same unit [30,31]. Further steps towards improved diagnosis in this heterogeneous patient group may require both C-peptide and GADA determinations, while additional markers could be developed following the recently described alterations in amino acid metabolism [32], in combination with determination of PAX4 risk haplotypes [33]. …”
Section: Discussionmentioning
confidence: 99%
“…KPD was divided into four subgroups according to the presence of glutamic acid decarboxylase (GAD) 65, GAD67, or IA-2 autoantibodies (A + or A − ) and β -cell functional reserve ( β + or β − ). The group distribution was A + β − , A − β + , A − β − , and A + β + [22, 23]. Choukem et al showed that β - and α -cell dysfunctions both contribute to the pathophysiology of KPD; in addition, KPD displays a defect in β -cell sensitivity to glucose and has reduced β -cell mass [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue of Diabetes , Patel et al (12) studied KPD patients with metabolomic approaches and then quantified metabolic fluxes using in vivo stable isotope tracers. This approach harnessed the high-throughput and broad information content of a metabolomic platform to generate hypotheses without the bias of a priori assumptions about disease-related metabolic derangements.…”
mentioning
confidence: 99%